Towards integrated water and energy works in the Netherlands Four asset management strategies for public value creation with public water works - van Buuren, Arwin; Grotenbreg, Sanne; Duijn, Mike; Roovers, Geert (International Journal of Water Governance, 2021)
Increasingly Dutch water authorities are considering to make their public (water) assets available for private initiatives to create more public value. However, developing multifunctional public water works asks for other ways of asset management. In this article we present a fourfold typology of styles of public asset management. We analyse – with help of an in-depth qualitative case comparison - four attempts to create public value, by using public water works for the production of sustainable energy. In particular we analyse which asset management strategy is used in these four cases and its effectiveness: how does this strategy evolve, to what extent does this strategy support private initiatives for multifunctional use of public water works and how does this ultimately result in value creation through such a broadened, multifunctional use? We conclude our paper with a couple of insights about the conditions under which the various asset management styles are both suitable and effective. Keywords: public value, asset management, public water works, strategy.